TRAF3IP3, a novel autophagy up-regulated gene, is involved in marginal zone B lymphocyte development and survival. (7th July 2015) - Peng, S; Wang, K; Gu, Y; Chen, Y; Nan, X; Xing, J; Cui, Q; Chen, Y; Ge, Q; Zhao, H
Summary: Tumour necrosis factor receptor-associated factor 3 (TRAF3) interacting protein 3 (TRAF3IP3; also known as T3JAM) is expressed specifically in immune organs and tissues. To investigate the impact of TRAF3IP3 on immunity, we generated Traf3ip3 knock-out (KO) mice. Interestingly, these mice exhibited a significant reduction in the number of common lymphoid progenitors (CLPs) and inhibition of B cell development in the bone marrow. Furthermore, Traf3ip3 KO mice lacked marginal zone (MZ) B cells in the spleen. Traf3ip3 KO mice also exhibited a reduced amount of serum natural antibodies and impaired T cell-independent type II (TI–II) responses to trinitrophenol (TNP)-Ficoll antigen. Additionally, our results showed that Traf3ip3 promotes autophagy via an ATG16L1-binding motif, and MZ B cells isolated from mutant mice showed a diminished level of autophagy and a high rate of apoptosis. These results suggest that TRAF3IP3 contributes to MZ B cell survival by up-regulating autophagy, thereby promoting the TI–II immune response.